Constitutive Expression of OsIAA9 Affects Starch Granules Accumulation and Root Gravitropic Response in Arabidopsis - Luo, Sha; Li, Qianqian; Liu, Shanda; Pinas, Nicholaas M.; Tian, Hainan; Wang, Shucai (Frontiers in Plant Science, 2015)
Auxin/Indole-3-Acetic Acid (Aux/IAA) genes are early auxin response genes ecoding short-lived transcriptional repressors, which regulate auxin signaling in plants by interplay with Auxin Response Factors (ARFs). Most of the Aux/IAA proteins contain four different domains, namely Domain I, Domain II, Domain III, and Domain IV. So far all Aux/IAA mutants with auxin-related phenotypes identified in both Arabidopsis and rice (Oryza sativa) are dominant gain-of-function mutants with mutations in Domain II of the corresponding Aux/IAA proteins, suggest that Aux/IAA proteins in both Arabidopsis and rice are largely functional redundantly, and they may have conserved functions. We report here the functional characterization of a rice Aux/IAA gene, OsIAA9. RT-PCR results showed that expression of OsIAA9 was induced by exogenously applied auxin, suggesting that OsIAA9 is an auxin response gene. Bioinformatic analysis showed that OsIAA9 has a repressor motif in Domain I, a degron in Domain II, and the conserved amino acid signatures for protein-protein interactions in Domain III and Domain IV. By generating transgenic plants expressing GFP-OsIAA9 and examining florescence in the transgenic plants, we found that OsIAA9 is localized in the nucleus. When transfected into protoplasts isolated from rosette leaves of Arabidopsis, OsIAA9 repressed reporter gene expression, and the repression was partially released by exogenously IAA. These results suggest that OsIAA9 is a canonical Aux/IAA protein. Protoplast transfection assays showed that OsIAA9 interacted ARF5, but not ARF6, 7, 8 and 19. Transgenic Arabidopsis plants expressing OsIAA9 have increased number of lateral roots, and reduced gravitropic response. Further analysis showed that OsIAA9 transgenic Arabidopsis plants accumulated fewer granules in their root tips and the distribution of granules was also affected. Taken together, our study showed that OsIAA9 is a transcriptional repressor, and it regulates gravitropic response when expressed in Arabidopsis by regulating granules accumulation and distribution in root tips.